Perceptions Regarding OERs: The Case of Prospective Teachers - Ahmad, Shamim (JOURNAL OF INDIAN EDUCATION, 2012)
Whatever its pedagogical credence or relevance, the open educational resource is above all an incredibly rich resource of learning, knowledge and research. At the turn of the twenty first century, its creation, dissemination and application are much more emphasised. This study examines the perceptions of prospective teachers regarding open educational resources (OERs). The methodology employed was descriptive survey and the subjects under investigation were chosen, based on simple random sampling from secondary teacher education programme. In the study, the investigator among other things found that the perceptions of prospective teachers regarding OERs are as production of educational resources and other learning management systems. The analysis brings forth that the OERs continue to be a potential resource to accelerate progress towards education, training and development for all. However, no significant difference was found when the subjects were compared with respect to the methodology of teaching, their gender and age groups. Considering OERs, as tool of education, training and development, link to the production and dissemination of knowledge, and the more recent perception as the agent of change in the learning process.